BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Frontiers in Fungal biotechnology and Plant Pathogen Relations. Edited by C. Manoharachary, G. Bagyanarayana, B. Bhadraiah, K. Satyaprasad, B.N. Reddy and A. Nagamani, Allied Publishers Limited, New Delhi, 2001, 500pp., Price Rs. 600.00 Diseases of Field Crops. Edited by V.K. Gupta and Y.S. Paul, Indus Publishing Company, New Delhi 110 027, Price Rs. 450.00 Predaceous Fungi by R. Dayal, Commonwealth Publishers, Darya Ganj, New Delhi, Price Rs. 850.00